2013
DOI: 10.1038/ncomms3204
|View full text |Cite
|
Sign up to set email alerts
|

Chemical influence on β-relaxations and the formation of molecule-like metallic glasses

Abstract: Secondary (also known as Johari-Goldstein or b-) relaxations are an intrinsic feature of supercooled liquids and glasses. They are important in many respects but the underlying mechanisms are not well understood. A long-standing puzzle is why some glasses show b-relaxations as pronounced peaks, whereas others as unobvious excess wings. Here we demonstrate that these different behaviours are related to the fluctuations of chemical interactions by using prototypical systems of metallic glasses. A general rule is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
96
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(117 citation statements)
references
References 52 publications
(87 reference statements)
11
96
0
Order By: Relevance
“…This shoulder is associated with a secondary process (β-relaxation) and, although with different degrees of intensity, was observed in all Pd-based alloys 3 . The presence of secondary relaxations has been found in many other metallic glasses 11,12 . In some systems, particularly La-based glasses, a distinguishable secondary relaxation is observed well separated from the α-peak [13][14][15] .…”
Section: Introductionmentioning
confidence: 77%
“…This shoulder is associated with a secondary process (β-relaxation) and, although with different degrees of intensity, was observed in all Pd-based alloys 3 . The presence of secondary relaxations has been found in many other metallic glasses 11,12 . In some systems, particularly La-based glasses, a distinguishable secondary relaxation is observed well separated from the α-peak [13][14][15] .…”
Section: Introductionmentioning
confidence: 77%
“…It is known that the flow phenomenon in MG is the percolation of the localized flow units 12,14,21 . To detect the extreme slow hidden flow before yielding or microscopic structural evolution during GLT, we applied Dynamical Mechanical Spectrum (DMS) measurement, which is a sensitive method to detect the viscoelastic properties of MGs [34][35][36] . The temperature dependence of the loss modulus E 00 measured at 1 Hz is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A La 60 Ni 15 Al 25 MG, with excellent glass-forming ability, thermal stability and unusual pronounced b-relaxation behaviour among known MGs 34,35 , is chosen as a model system. Plausible correlations among relaxation behaviours, dynamic heterogeneity, microscopic hidden inhomogeneous flow to macroscopic large-scale homogeneous flow during GLT transition and mechanical behaviours of MGs are established and interpreted by the energy landscape theory.…”
mentioning
confidence: 99%
“…It was also found that Co-based and Fe-based metallic glasses containing metalloid elements exhibit only relaxation behavior upon cryothermal cycling, which has a positive effect on the magnetic properties [50][51][52] . Atomic bonding was found to also be important in β-relaxation processes 53 . β-relaxation processes are directly correlated with the shear transformation zones, and therefore with the plasticity of glasses 54 .…”
Section: Discussionmentioning
confidence: 99%
“…However, there is still no generally accepted theory for β-relaxation. Yu et al 53 found that β-relaxation is more pronounced in systems with strong bonds between the constituent elements in the alloy system, while positive values or large fluctuations in the values of the enthalpy of mixing suppress β-relaxation.…”
Section: Discussionmentioning
confidence: 99%